Assessing Deep-Water Culture and Sand-Bed Aquaponics Systems for Lettuce (Lactuca sativa) Yield and Water Consumption - Salem, Lobna (AUC Knowledge Fountain, 2019)
Agriculture and aquaculture play an important role in food security and water withdrawals. Agriculture and aquaculture contribute to over 70% of global water consumption. Aquaponics provides a solution for both sectors to reduce the combined water consumption and pollution and increase food production. The goal of the present study was to assess two aquaponics systems Deep-Water Culture (DWC) and Sand-Bed lettuce (Lactuca sativa variety capitata Type Batavia) production and water consumption. Each system contained a fish tank, plant bed, collection bed, three replicates per system and a mechanical filter; whereas, DWC contained an additional biological filter after the mechanical filter. The main differences assumed between DWC and Sand-Bed are Sand-Bed uses less water and does not require biological filter as sand media acts like a biological filter. Both systems had similar nitrate and ammonium concentration over 35 days period. PH, temperature, EC, SAR and DO in both systems remained within acceptable ranges compared to literature. Sand-Bed nitrifying bacteria counts were also higher than DWC's bacteria by end of study period. Results showed that the lettuce root length in DWC were nearly two-fold the root length in Sand-Bed which provides larger surface area for nutrients uptake and enhance nitrification rate by bacteria. Calcium, phosphorous, zinc, copper, magnesium and boron concentrations in lettuce samples harvested form the DWC were nearly two-times the concentrations in lettuce samples growing in Sand- Bed. The DWC Lettuce yields per m2 were 27% higher than the Sand-Bed system's lettuce of 1.42 kg/m2 in DWC and 1.04 kg/m2 in Sand-Bed system. However, the daily water consumption in DWC system was higher than Sand-Bed system. Overall, DWC system performed better by producing higher lettuce yield with higher nutritional content while consuming more water compared to Sand bed system. Therefore, the Sand-Bed system requires further research to reach productive yields like the DWC system and benefit from its reduced water consumption and the potential of growing larger variety of crops.